The Impact of Service Quality and Customer Trust on Customer Loyalty Mediated by Customer Satisfaction in GOJEK Transportation Services - Kurniawati, Melinda; Fadhilah, Muinah; Ningrum, Nonik Kusuma (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to analyze the influence of service quality and customer trust on customer loyalty, with customer satisfaction as an intervening variable in GOJEK transportation services. A quantitative approach is used in this study with a descriptive method. The research sample consisted of 122 respondents selected using accidental purposive sampling technique. Data was collected through a questionnaire distributed via Google Forms, which was analyzed using statistical methods with IBM SPSS v.29 software. The research results indicate that service quality and customer trust have a positive and significant impact on customer loyalty, both directly and through customer satisfaction as an intervening variable. Customer satisfaction has also been shown to mediate the relationship between service quality and customer loyalty. However, customer satisfaction has not been able to mediate the relationship between customer trust and customer loyalty. This research provides important implications for transportation service companies in enhancing customer loyalty through improved service quality and building customer trust.